Synthesis of New Isolated Pyrazolo, Isoxazolo Derivatives Incorporating Pyrido[1,2]thiazinoquinoline - Ali Ahmed Elkanzi1, Nadia (Asian Journal of Chemistry, 2014)
Acetylation of 7,14-diamino-5,5a,12,12a-tetrahydro-[1,2]thiazino[4',5':5,6]pyrido[2,3-g][1,2]thiazino[5,4-b]quinoline-1,6,8,13(2H,4H, 9H,11H)-tetraone (1) with acetic anhydride and glacial acetic acid gave 2,9-diacetyl-7,14-diamino-5,5a,6a,7,12,12a-hexahydro-[1,2]thiazino[4',5':5,6]pyrido[2,3-g][1,2]thiazino[5,4-b]quinoline-1,6,8,13(2H,4H,9H,11H)-tetraone (2) The one-pot reaction of compound (2) with the aromatic aldehydes (3a-c) in the presence of catalytic amount of piperidine gave the corresponding arylidene derivatives (4a-c). Reaction of the arylidene derivatives (4a-c) with an equimolar amount of hydrazine hydrate and/or phenylhydrazine in the presence of a base gave N-acetylpyrazolo-derivatives (5a-c) and N-phenylpyrazolo derivatives (6a-c). Similarly, the isooxazolo pyrimidine derivatives (7a-c) were obtained through the reaction of arylidene derivatives (4a-c) with an equimolar amount of hydroxylamine hydrochloride in ethanol in the presence of sodium hydroxide as a catalyst. The structures of the new compounds were elucidated by compatible analytical and spectroscopic measurements.